Urgensi ilmu Al-qur’an dalam memahami pesan-pesan wahyu: Kajian konseptual dan implementatif - shofa, zahwa zahira (Maliki Interdisciplinary Journal, 2026)
The sciences of the Qur’an play a crucial role in enabling Muslims to understand divine revelations accurately and comprehensively. By studying aspects such as asbāb al-nuzūl, Makkiyyah–Madaniyyah, qirā’āt, abrogation, and the Qur’an’s linguistic structure, individuals can interpret Qur’anic verses more precisely within their historical, linguistic, and theological contexts. This article examines the urgency of Qur’anic sciences in understanding divine messages through both conceptual and implementative approaches. The conceptual dimension highlights the theoretical foundations of Qur’anic sciences, while the implementative dimension illustrates their application in interpretation and the development of moderate religious understanding. Strengthening mastery of these sciences fosters a deeper, more critical, and proportional comprehension of Islamic teachings, preventing misinterpretation or misuse of sacred texts. Thus, Qur’anic sciences remain a fundamental necessity in contemporary Islamic studies.